Amalgam Phase-Down Part 2: UK-Based Knowledge, Opinions, and Confidence in the Alternatives. (January 2022) - Bailey, O.; Vernazza, C.R.; Stone, S.; Ternent, L.; Roche, A.-G.; Lynch, C.
Introduction: Amalgam use has recently been phased down, and the potential for a phase-out is being investigated. Objectives: The study aimed to identify knowledge of the phase-down and opinions of a potential phase-out of amalgam by UK primary care clinicians and assess their confidence in using different materials in different situations. Methods: An anonymized, prepiloted cross-sectional e-survey was used to assess primary care clinicians' knowledge and opinions of the amalgam phase-down and potential phase-out and their confidence in using amalgam and the alternatives in different situations. In total, 11, 902 invitations were distributed through British dentist and therapist associations. Prior hypotheses were tested alongside descriptive statistics. Results: Response rate was 13% ( n = 1, 513). Knowledge of the amalgam phase-down was low, with just 3% clinicians correctly identifying all patient groups in whom amalgam use should be avoided in the United Kingdom. Postgraduate education on posterior composite placement was high (88%), but a large majority had personal and patient-centered concerns over the suitability of the alternatives and lacked confidence when placing composite in comparison to amalgam in difficult situations ( P < 0.0001). Logistic regressions revealed that the best predictors of high confidence in placing mesio-occluso-distal composites and composites in difficult situations were being a private general dentist or being primarily a composite user. Conclusion: Primary care clinicians have major personal and patient-centered concerns regarding the amalgam phase-down (of which they have limited knowledge) and potential phase-out. Many lack confidence in using the alternative, composite, to restore posterior teeth in difficult situations, whereas confidence in using amalgam in similar situations is high. Effective education of clinicians and understanding patients' needs, alongside policy changes, are required to enable a successful amalgam phase-down and potential phase-out. Knowledge Transfer Statement: This study shows that UK primary care clinicians are worried about the phase-down of amalgam for themselves and their patients. Many lack confidence in the alternative, composite, when used in difficult situations, which is in stark contrast to amalgam. Knowledge of the phase-down is limited. There is a need for more effective education of clinicians, an understanding of patients' values, and policy changes to ensure the success of the phase-down and potential phase-out of amalgam.